Design of Alarm Based Network Intrusion Detection System - Boskany, Najmadin Wahid (Sulaimani Journal for Pure and Applied Sciences, 2014)
Nowadays each computer network needs some tools in order to help their administrator for protecting network devices and data. These tools are ranging from firewall, antivirus, and intrusion detection systems. The main goal of this paper focuses on developing an applicable system for detecting intrusion and notifying network administrator from them (i.e. alert that there is unauthorized person attempts to break into network). The presented system can be used to detect intruders automatically depending on a signature file, and immediately notify onsite monitors and network administrator via alert message and short message. These different messages let them know who is going to access the network (i.e.; show the intruder IP address and used port number).
Keywords: Network Intrusion Detection; Short message; Logical Address; Socket Address,Application Programming Interface API; Alert Message